Digital asset ecosystems : rethinking crowds and cloud - Blanke, Tobias; ScienceDirect eBooks (Kidlington : Chandos Publishing, 2014)
This book reflects on the state of digital asset management and what the emerging 'web of things' could mean for managing, using and publishing digital assets. It introduces the emerging ecosystems of digital assets, examines digital asset management in a networked environment, and covers media ecosystems.
1. Introduction -- 2. Background -- 3. Methodologies and technologies -- 4. Open and closed digital asset ecosystems -- 5. Big data collecting -- 6. Economy and society of crowds and clouds -- 7. Conclusion.
Print version record.
Includes bibliographical references and index.
Elsevier
Keywords: Digital media; Cloud computing; Human computation; Electronic commerce; TECHNOLOGY & ENGINEERING -- Mechanical; Cloud computing; Digital media; Electronic commerce; Human computation; Digitala medier; Elektronisk handel; Datormoln; Electronic books